Gene Therapy Overexpressing Neuregulin 1 Type I in Combination With Neuregulin 1 Type III Promotes Functional Improvement in the SOD1G93A ALS Mice - Guillem Mòdol-Caballero; Guillem Mòdol-Caballero; Mireia Herrando-Grabulosa; Mireia Herrando-Grabulosa; Sergi Verdés; Sergi Verdés; Belén García-Lareu; Belén García-Lareu; Neus Hernández; Neus Hernández; Isaac Francos-Quijorna; Isaac Francos-Quijorna; et al. (Frontiers in Neurology, 2021)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease affecting the neuromuscular system for which currently there is no effective therapy. Motoneuron (MN) degeneration involves several complex mechanisms, including surrounding glial cells and skeletal muscle contributions. Neuregulin 1 (NRG1) is a trophic factor present particularly in MNs and neuromuscular junctions. Our previous studies revealed that gene therapy overexpressing the isoform I (NRG1-I) in skeletal muscles as well as overexpressing the isoform III (NRG1-III) directly in the central nervous system are both effective in preserving MNs in the spinal cord of ALS mice, opening novel therapeutic approaches. In this study, we combined administration of both viral vectors overexpressing NRG1-I in skeletal muscles and NRG1-III in spinal cord of the SOD1G93A mice in order to obtain a synergistic effect. The results showed that the combinatorial gene therapy increased preservation of MNs and of innervated neuromuscular junctions and reduced glial reactivity in the spinal cord of the treated SOD1G93A mice. Moreover, NRG1 isoforms overexpression improved motor function of hindlimb muscles and delayed the onset of clinical disease. However, this combinatory gene therapy did not produce a synergic effect compared with single therapies, suggesting an overlap between NRG1-I and NRG1-III activated pathways and their beneficial effects.